(untitled) (Revista de Estudios Europeos, 2026)
The present article aims to study carefully the current legal status of the Iberian wolf both European Union legislation and national Spanish legislation, without forgetting its previous legal status and recent modifications which have been implemented, as well as future prospects. In this regard, and in light of controversies have been arisen, recent case-law will be analyse, in particular, Judgment of CJEU (First Chamber) of 24th July 2024, c. 436/22, which dissipates all doubts regarding legal status of the animal, the consequences of its cataloguing, and possible applicable measures. To this end, Habitats Directive regarding canis lupus, the principles of precaution and caution and the requirement of scientific evidence concerning the implementation of management measures, will be examined. Last but not least, the appeal of unconstitutionality filed by the Spanish Ombudsman against Law 1/2025 on the prevention of food loss and food waste will be briefly addressed.